A Compliance Audit Model on the Government Grant Management in Indonesia - Hafiz, Muhammad Shareza; Wahyuni, Sri Fitri; Wulandari, Tri (AIBPM Publisher, 2023)
This study evaluates the challenges and accuracy needed to apply Covid-19 social welfare funds in Indonesia, according Ministry of Social Affairs Regulation No. 20 of 2019. This study also seeks to understand the causes of Indonesians’ limited assistance adoption. Purposive sampling is used in this qualitative investigation. Researchers collected empirical data through qualitative interviews and used QSR NVivo 12 for data analysis. The Head of the Environment meticulously collected beneficiary data to start government grant management in North Sumatra. After that, the Village Office and top authorities arranged a well-organized assistance distribution campaign. Under the direction of the Head of the Environment, local resources were allocated to registered community members. Ministerial Regulation No. 20 of 2019 from the Ministry of Social Affairs governs government grant administration in North Sumatra. Dual engagement in the local community may explain the aid shortfall in North Sumatra, according to studies. People who accept and refuse social help are examples of this.